Contemporaries of Erasmus : a biographical register of the Renaissance and Reformation. - Bietenholz, Peter G.; Deutscher, Thomas Brian, 1949-; Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974., 1985)
Offers biographical information about the more than 1900 people mentioned in the correspondence and works of Erasmus who died after 1450 and were thus approximately his contemporaries.